QUALITY INDICATOR OF TRANSLATION TEXT - Illiyin, Nur Kholifatul; Ibtisam, Ibtisam (Universitas Muhammadiyah Semarang, 2019)
This articel is written to explain the indicator in determining the quality of a translation. The background of the writting in this article is a support in conducting a criticsm of the translation and the existence of differences in paradigms between the researchers of translation with one another. Writing of the article aims to facilitate in determining the quality and feasibiliity of a translation said to be translation. the result of writing this article is that research is carried out on a translation so that the object being studied is the product of translation process.